Translational Research in Cancer 2021
DOI: 10.5772/intechopen.90806
|View full text |Cite
|
Sign up to set email alerts
|

IL10 as Cancer Biomarker

Abstract: Chronic inflammation can trigger events that would induce the malignant transformation of cells and carcinogenesis. Cytokines play a crucial role and can control the development and multiplication of cancerous cells. However, clinical data present controversy about the participation of these proteins in the establishment and development of cancer. Interleukin 10 (IL-10), a potent anti-inflammatory cytokine, has been the subject of multiple studies. Several studies have reported that IL-10 has pro-and antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…In TME IL-10 is mainly produced by M2 macrophages and Th2 cells but also monocytes, mast cells, Treg cells, and by subsets of activated T and B cells [ 62 ]. This cytokine plays a primarily immune suppressive role in TME.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In TME IL-10 is mainly produced by M2 macrophages and Th2 cells but also monocytes, mast cells, Treg cells, and by subsets of activated T and B cells [ 62 ]. This cytokine plays a primarily immune suppressive role in TME.…”
Section: Reviewmentioning
confidence: 99%
“…Immune suppressive and tumor-promoting action of IL-10 was supported by finding that IL-10 deficiency enhanced the efficacy of DC-based immunotherapy, reduced MDSC and Treg levels in the TME, and promoted Th1-type antitumor responses in mice [ 70 ]. In contrast, in vitro studies have shown, that low levels of IL-10 could exert the antitumor effect via activation of NK cells, T lymphocytes, and macrophages [ 62 ]. These data show that the role of IL-10 still has to be fully explained.…”
Section: Reviewmentioning
confidence: 99%
“…3E ) (46). The B-lymphoid lineage of T/My MPAL showed significant enrichment of the IL-10 pathway that has been extensively explored as a prognostic marker for leukemias (47). Also, in T/My MPAL B cells, the upregulated CSK pathway is associated with the promotion of B-cell activation, while the IFN-γ pathway is associated with inhibition of B-cell activation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that cancer cells can synthesize themselves, thereby causing an imbalance in the homeostasis of the immune system and causing tumors to escape. 13…”
Section: Resultsmentioning
confidence: 99%